(untitled) (Bangladesh Agronomy Journal, 2017)
A pot experiment with six aman rice varieties viz. BRRI dhan34, BRRI dhan38, Binadhan-9, Binadhan-13, Kalijira and Rajbhogh was conducted at the experimental shed of the Department of Agronomy, Sher-e Bangla Agricultural University, Dhaka during the period of June- December, 2014 to investigate the effect of salinity on the growth, physiology and yield of some aromatic rice under different salt stress conditions. The experiment was carried out with five salt stress treatments viz. control (without salt), S25 (25 mM NaCl), S50 (50 mM NaCl), S75 (75 mM NaCl) and S100 (100 mM NaCl). Salt stress significantly reduced the plant height, tiller hill-1 and leaves hill-1 of these varieties at all growth duration. Among the varieties Binadhan-9 and BRRI dhan38 performed better under saline condition. On the other hand, local variety Kalijira did not perform well under saline condition. Bangladesh Agron. J. 2016, 19(2): 1-10